Effects of work requirements for food assistance eligibility on disability claiming - Sarah S. Stith (IZA Journal of Labor Economics, 2022)
Between 2010 and 2017, 42 U.S. states added work requirements as a food assistance eligibility criterion for Able-Bodied Adults Without Dependents (ABAWDs). Another U.S. public assistance program, Supplemental Security Income (SSI), provides food assistance without a work requirement, along with cash transfers and health insurance. Therefore, individuals for whom working is difficult may be induced to opt out of the labor force and into SSI in order to maintain access to food assistance. This study is the first to examine whether work requirements associated with food assistance eligibility lead to an increase in SSI applications and receipts. Based on difference-in-differences and event study analyses of comprehensive administrative claims data from the Social Security Administration and survey data from the Current Population Survey, this study finds evidence of lagged effects on SSI applications overall, and reduced Supplementary Nutritional Assistance Program (SNAP) receipts followed by a delayed smaller increase in SSI receipts among individuals with self-reported disabilities. While most SSI applications induced by SNAP-related work requirements appear to be unsuccessful, a small, vulnerable population may move out of the workforce and into SSI in response to the implementation of work requirements.
Keywords: H53; I38; J22; 330; disability; public assistance; work requirement; food stamps; time limit waiver; welfare